Penerapan Model Turnamen dengan Fun Frame In Physics Pada Pembelajaran Tentang Hukum Induksi Elektromagnetik Faraday - Cahyo Permadi; Made R. S. Shanti. N.A. Shanti. N.A.; Alvama Pattiserlihun (Universitas Muhammadiyah Purworejo, 2018)
Abstract – Learning media is indispensable in the phase of consolidation with an effort involving students actively and assist student in understanding the material. This research aims to make Fun Frame in Physics (FFP) learning media design and investigate the effectiveness of FFP with the topic of electromagnetic induction at the consolidation stage. This research is a descriptive research. Respondents to this study were 14 - 16 junior high school students of class IX. The research instruments include questionnaire for material experts, questionnaires for media expert, student observation sheets, student activity observation sheets and student reponse observation sheets. All data obtained were analyzed qualitative decriptive. Based on student answers, the average value of each group ranges from 75 to 87,5. Based on the results of the validation, material experts and media experts gave a positive response, 83,38% and 93,6% respectively. Based on the questionnaires, 86,68% of students responded positively to the FFP media. Based on student activity observation sheets, 86,81% of student were active in group activity. So FFP is effective to assist students in understanding the topic of electromagnetic induction and can be a reference in the consolidation phase